Monotone Positive Solution of Nonlinear Third-Order BVP with Integral Boundary Conditions - Sun Jian-Ping; Li Hai-Bao (Boundary Value Problems, 2010)
This paper is concerned with the following third-order boundary value problem with integral boundary conditions , where and . By using the Guo-Krasnoselskii fixed-point theorem, some sufficient conditions are obtained for the existence and nonexistence of monotone positive solution to the above problem.